Population control of Meloidogyne sp. in areas cultivated with vegetables using cover crops (Research, Society and Development, 2021)
One of the pillars of the no-tillage system (NTS) is crop rotation, done in a planned way to meet the desired objective, which, among others, can assist in the control of existing phytonematodes in the soil. The objective of this study was to quantify the biomass of cover plants and the control carried out on the population of phytomatomatoids present in the area. The study was conducted in Uberaba, MG, in a Typic Hapludox, with a clayey-sandy texture. The design used was completely randomized, where four treatments were evaluated for the population control of phytonematodes: 1- Sunn hemp; 2- Pearl millet; 3- Chemical treatment (Soybean NA5909RG with nematicide Fluensulfona); 4- Fallow (spontaneous vegetation = control), with five repetitions. Sampling was carried out to evaluate the fresh (MF) and dry (DM) mass of the coverings in areas of 2m2. For nematological analysis, samples were taken before planting, at 45 and 90 days after planting (DAP), with 5 soil samples being collected in each plot, at a depth of 0.30 m layer. The production of MF and MS crotalaria and millet was 10.3 and 46.5% higher than fallow, respectively. In the treated soybean plots (chemical treatment), 90 DAP, the largest population of phytonematodes was found, followed by fallow, millet and crotalaria. The management of rotalaria and millet in NTS provide a population control of Meloidogyne incognita, equivalent to 95 and 93%, respectively, while chemical treatment and control reduced population infestation by 8%.